1997
DOI: 10.1093/protein/10.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of transmembrane alpha-helices in prokaryotic membrane proteins: the dense alignment surface method

Abstract: A new, simple method for predicting transmembrane segments in integral membrane proteins has been developed. It is based on low-stringency dot-plots of the query sequence against a collection of non-homologous membrane proteins using a previously derived scoring matrix [Cserzö et al., 1994, J. Mol. Biol., 243, 388-396]. This so-called dense alignment surface (DAS) method is shown to perform on par with earlier methods that require extra information in the form of multiple sequence alignments or the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
609
0
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 963 publications
(635 citation statements)
references
References 1 publication
13
609
0
7
Order By: Relevance
“…To identify conserved domains in FdTonB we analysed the sequence using the National Center for Biotechnology Information (NCBI) Conserved Domains Database (Marchler-Bauer et al, 2009). Putative transmembrane regions were identified using the DAS Transmembrane Prediction server (Cserzö et al, 1997). Sequence similarity analysis to detect FdTonB homologues was conducted using the NCBI BLAST program (Altschul et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify conserved domains in FdTonB we analysed the sequence using the National Center for Biotechnology Information (NCBI) Conserved Domains Database (Marchler-Bauer et al, 2009). Putative transmembrane regions were identified using the DAS Transmembrane Prediction server (Cserzö et al, 1997). Sequence similarity analysis to detect FdTonB homologues was conducted using the NCBI BLAST program (Altschul et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Using the DAS Transmembrane Prediction server (Cserzö et al, 1997), we identified the domain encompassing amino acids 21-41 as a putative transmembrane domain. A conserved SXXXH motif (amino acids 29-33), which delimits the minimum required energy-transduction element of TonB proteins, is found within the predicted transmembrane a-helix ( Fig.…”
Section: Bioinformatic Analysis Of Fdtonbmentioning
confidence: 99%
“…Although Lpp signal peptide cleavage sites are not predicted, the graphical display from this service was particularly useful as it provided an indication of the lengths of predicted signal peptide n-and h-regions relative to the position of the possible lipobox cysteine. Where sequence features required further clarification, other methods for predicting transmembrane domains were also applied including TopPred2 (Claros & von Heijne, 1994 ; http :\\bioweb.pasteur.fr\seqanal\interfaces\ toppred.html) and DAS (Cserzo et al, 1997 ;http :\\www. sbc.su.se\"miklos\DAS\).…”
Section: Methodsmentioning
confidence: 99%
“…This process was repeated iteratively until most of the amino acids were below 95% cutoff value and residue which lies above 95% cutoff value were subjected to loop modeling in MODELLER. Finally, GPR87 model showing the best PROCHECK and ERRAT plot was then subjected to native protein folding energy evaluation using ProSA server (Wiederstein et al, 2007 DOI:http://dx.doi.org/10.7314/APJCP.2013.14.12.7473 Computational 3-D Analysis of Human GPR87 Protein of: Implications for Structure-Based Drug Design Transmembrane helices prediction and function assignment of GPR87 protein Different servers like DAS, TMHMM, HMMTOP, TMpred, TopPred, SOSUI, SPLIT, and Predictprotein (PHD) servers were accessed to predict and validate the transmembrane helical region (TM region) of GPR87 protein (Hofmann et al, 1993;Claros et al, 1994;Cserzo et al, 1994;Hirokawa et al, 1998;Tusnády et al, 1998;Krogh et al, 2001;Juretic et al, 2002;Jones et al, 2004;Rost et al, 2004). To know the novel functions of GPR87 protein by using a SVMProt server with the aim of support vector machine learning techniques (SVM) which classifies protein into functional families from its primary sequences i.e.…”
Section: Model Validationmentioning
confidence: 99%